Analysis of Emotional Intelligence in Table Tennis Players at Indonesia University of Education Using the TMMS-24 Method - Diftha Nusa Al fitra; Mohammad Zaky; Septian Williyanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study examines emotional intelligence as an important factor in competitive sports, mainly table tennis, as table tennis is a sport that needs a high level of concentration and self control. The aim of this study is to analyse the level of emotional intelligence of table tennis players at Indonesian University of Education. Using a descriptive quantitative method with 50 respondents, the Trait Meta Mood Scale (TMMS-24) instrument was employed, which has three main dimensions emotional attention, emotional clarity, and emotional regulation. Data analysis was performed descriptively using SPSS version 22. The results of the study indicate that the players have a good level of emotional intelligence in all three dimensions, with an average score of 29.98 for emotional attention 30.60 for emotional clarity, and 33.18 for emotional regulation. This demonstrates the players capability to identify, understand, and manage their emotions effectively, as well as when on competitive pressure. Altogether, these finds conclude that emotional intelligence plays a vital role in the the mental stability and performance of table tennis players. Hence, players and coaches are urged note attention to emotional intelligence for the development of long termn menta endurance and the grow performance of table tennis players.